A two-sample Mendelian randomization study reveals the causal effects of statin medication on gut microbiota abundance in the European population - Zhou, Peng; Qiu, Chen; Zhuang, Zequn; Shi, Kaihang; Yang, Zhihui; Ding, Yuyan; Qu, Huiheng; Xia, Jiazeng (Frontiers in Genetics, 2024)
BackgroundObservational studies have reported changes in gut microbiota abundance caused by long-term statin medication therapy. However, the causal relation between statin medication and gut microbiota subsets based on genetic variants remains unclear.MethodsWe used genome-wide association study (GWAS) data on statin medication from the FinnGen database and gut microbiota abundance GWAS data from the IEU OpenGWAS project. A Mendelian randomization (MR) analysis was conducted to evaluate the causal effect of statin medication on gut microbiota abundance using the inverse variance weighting (IVW) method, MR-Egger regression, and weighted median approach. Meanwhile, heterogeneity and pleiotropy analyses were also undertaken in this study.ResultsStatin medication was negatively correlated with five species of gut microbiota abundance: Parabacteroides (BetaIVW = −0.2745, 95% CI = (−0.4422, −0.1068), and PIVW = 0.0013), Ruminococcaceae UCG-009 (BetaIVW = −0.1904, 95% CI = (−0.3255, −0.0553), and PIVW = 0.0057), Coprococcus 1 (BetaIVW = −0.1212, 95% CI = (−0.2194, −0.0231), and PIVW = 0.0154), Ruminococcaceae UCG-010 (BetaIVW = −0.1149, 95% CI = (−0.2238, −0.0060), and PIVW = 0.0385), and Veillonellaceae (BetaIVW = −0.0970, 95% CI = (−0.2238, 0.0060), and PIVW = 0.0400) and positively correlated with one species of gut microbiota: Desulfovibrio (BetaIVW = 0.2452, 95% CI = (0.0299, 0.4606), and PIVW = 0.0255). In addition, no significant heterogeneity or pleiotropy was detected in the abovementioned gut microbiota.ConclusionThis Mendelian randomization analysis indicates a causal relationship between statin medication and six gut microbiota species. These findings may provide new strategies for health monitoring in populations taking long-term statin medications.